Confucianism in China’s Nationally Oriented Advertising Text - Yu. Wang (Tsentr nauchnykh i obrazovatelnykh proektov, 2021)
The article is devoted to the multimodal analysis of the representation of the national-cultural phenomenon “Confucianism” in the field of advertising in modern China on the examples of nationally-oriented advertising texts of different thematic varieties. The relevance of the work is due to the importance of preserving and continuing the heritage of Confucianism in modern Chinese society, especially in the media space. Particular attention is paid to the multimodal analysis of verbal and non-verbal means of expressing the key concept of Confucianism “five constancies of a righteous person” in Chinese nationally oriented advertising texts. It is shown that the concept of “five permanencies” as one of the important components of Confucianism gets its continuation in the field of advertising in modern China, develops in accordance with the social life of the Chinese people in the modern era. It has been established that the use of the Confucian idea of the five permanencies of a righteous person can be considered as one of the most important and effective ways to create advertising with the aim of influencing the target audience of the Chinese domestic market. The conclusions and results of the study allow us to get a general idea of the concept of the five constancies of Confucianism, as well as the practice of its application as methods of manipulating public consciousness in modern Chinese advertising, which is of great importance for sinological research in various scientific fields.